Explaining School Enrolment Trends in Kerala, India - Janakumaran Nair Retnakumar and Perianayagam Arokiasamy (Journal of South Asian Development 2006; 1; 231, 2006)
An inevitable consequence of demographic transition in the Indian state of Kerala is the rapidly declining school enrolment in government-funded lower primary schools. So far studies dealing with demographic transition and falling school enrolment concluded that fertility decline is the sole reason for this. A major limitation of these studies is that they focused only on students enrolled in schools affiliated to the Directorate of Public Instruction without accounting for the enrolments of parallel fee-charging private unaided English-medium schools in the state. Based on the enrolment statistics of the Directorate of Public Instruction, studies argued that fertility decline is the main reason for school enrolment decline, leading to the emergence of uneconomic schools. Our analysis shows that aside from fertility decline, the poor quality of teaching in government-funded schools and the resultant exodus to private unaided English-medium schools is significant in accounting for decline in enrolments. The retention of students in government-funded schools can be sustained only by improving the quality of school education.